2018
DOI: 10.1101/241919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding the balance between model complexity and performance: Using ventral striatal oscillations to classify feeding behavior in rats

Abstract: Binge eating is a disruptive and treatment-resistant behavior that complicates the management of obesity and comorbid psychiatric disorders. The distributed network that governs feeding behavior, particularly of palatable food, has a nexus point within the ventral striatum (VS). This important structure integrates information from energy homeostasis circuits of the hypothalamus and brain stem, cognitive control regions of the prefrontal cortex and central nodes of learning and memory. The VS is thus an ideal t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Although cannabis use in schizophrenia is primarily observed in male patients 66 , previous studies have suggested that considerable sex differences exist in the oscillatory biomarkers associated with psychopathology 43 , warranting the assessment of sex as a biological variable in the measures assessed here. Future investigations will be performed using the same protocol to detect any changes in schizophrenia-like behaviours after acute and chronic cannabis vapour exposure using the NVHL rat, as past investigations indicate that THC-induced reductions in oscillatory activity relate to deficits in sensorimotor gating and working memory 36 67 ; we will also aim to identify which electrophysiological features are related to behavioural deficits 68 . Additionally, understanding how cessation of cannabis use impacts aberrant oscillatory activity may help further characterize the causal contribution of oscillatory activity to effects of cannabis vapour exposure on the symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Although cannabis use in schizophrenia is primarily observed in male patients 66 , previous studies have suggested that considerable sex differences exist in the oscillatory biomarkers associated with psychopathology 43 , warranting the assessment of sex as a biological variable in the measures assessed here. Future investigations will be performed using the same protocol to detect any changes in schizophrenia-like behaviours after acute and chronic cannabis vapour exposure using the NVHL rat, as past investigations indicate that THC-induced reductions in oscillatory activity relate to deficits in sensorimotor gating and working memory 36 67 ; we will also aim to identify which electrophysiological features are related to behavioural deficits 68 . Additionally, understanding how cessation of cannabis use impacts aberrant oscillatory activity may help further characterize the causal contribution of oscillatory activity to effects of cannabis vapour exposure on the symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to link corticostriatal activity to biological sex or phase of estrous we used an unbiased machine learning approach similar to what we have published previously (30,31). We built predictive models using corticostriatal LFPs to classify rats by biological sex and female rats by phase of estrous.…”
Section: Discussionmentioning
confidence: 99%
“…We used a similar machine learning approach (as described above) to link corticostriatal activity to alcohol intake levels, except the outcomes were continuous (g/kg of alcohol consumed by each rat across each day) rather than binary. If the lasso indicated that information existed in the LFP signal, we implemented exhaustive single feature regressions using each LFP predictor to determine the relative information content of each feature, as we have previously described in detail (31).…”
Section: Linking Corticostriatal Lfps To Alcohol Intake Levelsmentioning
confidence: 99%
“…In the ventral striatum (vStr), a brain structure involved in the motivational control of behavior, several conditions are in place to suggest that oscillations can usefully inform studies of its function. First, the vStr LFP shows a full spectrum of rhythmic activity, including prominent gamma-band oscillations but also delta, theta, and beta-band activity, which are modulated in association with behavior and task variables and relate to local spiking activity (Leung and Yim, 1993; van der Meer and Redish, 2009; Berke, 2009; Kalenscher et al, 2010; Howe et al, 2011; Donnelly et al, 2014; Dejean et al, 2017; Dwiel et al, 2019). Manipulations of the dopaminergic and endocannabinoid system modify vStr LFP oscillations (Berke, 2009; Lemaire et al, 2012; Morra et al, 2012) and drug and disease states are associated with altered striatal LFPs (Dejean et al, 2017; Naze et al, 2018; Wu et al, 2018; Hultman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%